The Complement C3a and C3a Receptor Pathway in Kidney Diseases - Gao, Shuang; Cui, Zhao; Zhao, Ming-hui (Frontiers in Immunology, 2020)
The pathogenesis of some kidney diseases is closely associated with complement activation, where the C3a/C3a receptor (C3aR) might play a crucial role. C3a/C3aR has dual roles and may exert anti-inflammatory or pro-inflammatory effects depending on different cell types and diseases. In the kidneys, C3aR is primarily expressed on the tubular epithelium and less in glomerular podocytes. C3aR expression is enhanced and the levels of C3a in the plasma and urine are increased in kidney diseases of several types, and are associated with disease progression and severity. The C3a/C3aR pathway facilitates the progression of glomerular and tubulointerstitial diseases, while it has opposite effects on urinary tract infections. Clinical trials targeting C3a/C3aR in kidney diseases are lacking. Here, we reviewed the studies on the C3a/C3aR pathway in kidney disease, with the aim of understanding in-depth its controversial roles and its potential therapeutic value.